2011
DOI: 10.1007/s11517-011-0761-z
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for recording neuronal depolarization with recording at 125–825 Hz: implications for imaging fast neural activity in the brain with electrical impedance tomography

Abstract: Electrical impedance tomography (EIT) is a recently developed medical imaging method which has the potential to produce images of fast neuronal depolarization in the brain. Previous modelling suggested that applied current needed to be below 100 Hz but the signal-to-noise ratio (SNR) recorded with scalp electrodes during evoked responses was too low to permit imaging. A novel method in which contemporaneous evoked potentials are subtracted is presented with current applied at 225 Hz to cerebral cortex during e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
79
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(92 citation statements)
references
References 37 publications
13
79
0
Order By: Relevance
“…Previous measurements of cortical impedance changes during evoked activity in the cortex include those undertaken by Aristovich et al (2016) and Oh et al (2011); they reported maximum amplitudes of 0.007% and 0.1% respectively. In the current work the cortical impedance change had a larger mean amplitude of À0.16 AE 0.08%.…”
Section: Do Recorded Signals From Cortex and Thalamus Match The Litermentioning
confidence: 99%
See 1 more Smart Citation
“…Previous measurements of cortical impedance changes during evoked activity in the cortex include those undertaken by Aristovich et al (2016) and Oh et al (2011); they reported maximum amplitudes of 0.007% and 0.1% respectively. In the current work the cortical impedance change had a larger mean amplitude of À0.16 AE 0.08%.…”
Section: Do Recorded Signals From Cortex and Thalamus Match The Litermentioning
confidence: 99%
“…Multiple transfer impedance measurements are obtained through the use of a switch network which allows current to be sequentially injected through different electrode pairs. Fast neural EIT can detect impedance changes associated with ion channel opening during neuronal depolarisation (Klivington and Galambos, 1967;Oh et al, 2011;Velluti et al, 1968). Impedance changes arise as injected current, normally confined to the extracellular space due to the high membrane capacitance of neurons, can pass through open ion channels in the membrane and additionally travel in the intracellular space.…”
Section: Introductionmentioning
confidence: 99%
“…Existing EIT systems include the KHU [12], fEITER [13], Dartmouth EIT System [14], Xian EIT system [15], Swisstom Pioneer Set (Swisstom AG, Switzerland) and systems previously developed in our laboratory at UCL [16,17]. Typically these systems have at least 32 electrodes with voltages recorded in parallel to increase frame rate, Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…EIT has the potential to provide a uniquely useful new imaging method in clinical or experimental neuroscience, 4 enabling the imaging of epileptic seizures 5 and bloodflow changes during cortical evoked activity 6 in humans, and of cortical spreading depression 7,8 and fast neuronal depolarization 9,10 in anaesthetized animals. Furthermore, its noninvasiveness and the fact that it does not involve ionizing radiation make EIT a potential method of continuous monitoring.…”
Section: Introductionmentioning
confidence: 99%